1991
DOI: 10.1111/j.1365-2796.1991.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Features of Sjögren's syndrome in patients with primary biliary cirrhosis

Abstract: Twenty-six consecutive patients with primary biliary cirrhosis (PBC) from northern Sweden were studied regarding the occurrence and features of Sjögren's syndrome (SS). In more than 50% of the patients the rose bengal dye test showed conjunctival and/or corneal staining. In six patients keratoconjunctivitis sicca (KCS) was present with positive rose bengal and Schirmer tests. In a further three patients only the results of the Schirmer tests were abnormal. Radiological findings of sialectasia were demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
3
22
0
3
Order By: Relevance
“…Among autoimmune conditions found in PBC cases, Raynaud syndrome (12%) and Sjögren syndrome (10%) were the most frequent, in accordance with previous reports. 22,23 We note that other studies reported higher prevalence rates but were based on a smaller number of probably select cases. We found that 27 cases (3%) with PBC reported a diagnosis of SLE.…”
Section: Discussionmentioning
confidence: 88%
“…Among autoimmune conditions found in PBC cases, Raynaud syndrome (12%) and Sjögren syndrome (10%) were the most frequent, in accordance with previous reports. 22,23 We note that other studies reported higher prevalence rates but were based on a smaller number of probably select cases. We found that 27 cases (3%) with PBC reported a diagnosis of SLE.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast to AIH, the most frequently associated CAIDs in PBC is the Sjogren's syndrome, which has been reported in the literature with a wide proportion of cases ranging from 20% to nearly 80% [91][92][93][94][95][96] . Two large cohort studies from the United Kingdom and Italian groups have identified Sjogren's syndrome as the most prevalent CAIDs with 25 and 34% in patients with PBC respectively [97,98] .…”
Section: Comparisons With Pbcmentioning
confidence: 99%
“…Two large cohort studies from the United Kingdom and Italian groups have identified Sjogren's syndrome as the most prevalent CAIDs with 25 and 34% in patients with PBC respectively [97,98] . The target antigen in salivary gland ducts of patients with Sjogren's has been shown in the bile duct epithelium of PBC patients [96] . In a population-based cohort study in the United Kingdom, 53% of patients with PBC had one or more CAIDs [97] .…”
Section: Comparisons With Pbcmentioning
confidence: 99%
“…Various anti thyroid antibodies, such as antimicrosomal or antithyroglobulin antibodies, are present in a large percentage of patients [ 17,47], Associations of scleroderma, arthropathy and Sjogren's syndrome with PBC have been well described. Scleroderma may be present in 3-4% of PBC patients [48] while symptom atic inflammatory arthritis is reported in 4 -42% of patients [49], Sjorgren's syndrome de fined by the presence of (1) dry eyes (kerato conjunctivitis sicca) and/or xerostomia, and (2) autoimmune disease is seen in 72-100% of patients [1,50].…”
Section: Associated Diseasesmentioning
confidence: 99%